\(L^p\)-approximation \((p ≥ 1)\) by Stancu-Kantorovich polynomials - Finta, Zoltán (Rev. Anal. Numér. Théor. Approx., 2002)
We establish direct and converse estimates for a generalized Kantorovich polynomial operator depending on a positive parameter.